Health-Promoting Properties of Lactobacillus helveticus - Taverniti, Valentina; Guglielmetti, Simone (Frontiers in Microbiology, 2012)
Lactobacillus helveticus is an important industrial thermophilic starter that is predominantly employed in the fermentation of milk for the manufacture of several cheeses. In addition to its technological importance, a growing body of scientific evidence shows that strains belonging to the L. helveticus species have health-promoting properties. In this review, we synthesize the results of numerous primary literature papers concerning the ability of L. helveticus strains to positively influence human health. Several in vitro studies showed that L. helveticus possesses many common probiotic properties, such as the ability to survive gastrointestinal transit, adhere to epithelial cells and antagonize pathogens. In vivo studies in murine models showed that L. helveticus could prevent gastrointestinal infections, enhance protection against pathogens, modulate host immune responses, and affect the composition of the intestinal microbiota. Interventional studies and clinical trials have also demonstrated a number of health-promoting properties of L. helveticus. Finally, several studies suggested that specific enzymatic activities of L. helveticus could indirectly benefit the human host by enhancing the bioavailability of nutrients, removing allergens and other undesired molecules from food, and producing bioactive peptides through the digestion of food proteins. In conclusion, this review demonstrates that in light of the scientific literature presented, L. helveticus can be included among the bacterial species that are generally considered to be probiotic.